Cerium Oxide Nanoparticles Re-establish Cell Integrity Checkpoints and Apoptosis Competence in Irradiated HaCat Cells via Novel Redox-Independent Activity - Caputo, Fanny; Giovanetti, Anna; Corsi, Francesca; Maresca, Vittoria; Briganti, Stefania; Licoccia, Silvia; Traversa, Enrico; Ghibelli, Lina (Frontiers in Pharmacology, 2018)
Cerium oxide nanoparticles (CNPs) are potent radical scavengers protecting cells from oxidative insults, including ionizing radiation. Here we show that CNPs prevent X-ray-induced oxidative imbalance reducing DNA breaks on HaCat keratinocytes, nearly abating mutagenesis. At the same time, and in spite of the reduced damage, CNPs strengthen radiation-induced cell cycle arrest and apoptosis outcome, dropping colony formation; notably, CNPs do not possess any intrinsic toxicity towards non-irradiated HaCat, indicating that they act on damaged cells. Thus CNPs, while exerting their antioxidant action, also reinforce the stringency of damage-induced cell integrity checkpoints, promoting elimination of the “wrong” cells, being in fact radio-sensitizers. These two contrasting pathways are mediated by different activities of CNPs: indeed Sm-doped CNPs, which lack the Ce3+/Ce4+ redox switch and the correlated antioxidant action, fail to decrease radiation-induced superoxide formation, as expected, but surprisingly maintain the radio-sensitizing ability and the dramatic decrease of mutagenesis. The latter is thus attributable to elimination of damaged cells rather than decreased oxidative damage. This highlights a novel redox-independent activity of CNPs, allowing selectively eliminating heavily damaged cells through non-toxic mechanisms, rather reactivating endogenous anticancer pathways in transformed cells.